Reasons for Cancellation of Operation on the Day of Intended Surgery in Tripoli University Hospital, Libya - Dalal Almghairbi; Zenab Elfzzani; Soad Abouessa; Khalid Aljarmi (AlQalam Journal of Medical and Applied Sciences, 2025)
Frequent cancellations of scheduled operations are a major reason for ineffective use of operating room time and the wastage of valuable resources. These cancellations not only disrupt hospital operations but also cause emotional distress for patients and negatively impact the perceived quality of healthcare services. In Libya, the reasons for surgical cancellation remain unknown. The current study aims to investigate the causes behind the cancellation of scheduled operations on the day of surgery (for both adult and paediatric patients) at Tripoli University Hospital (TUH) in Libya. A prospective observation study was conducted over six months, from June to December. Data was collected by using a standardised form completed by anaesthetists on the day of surgery. The data collection form is divided into administrative/logistic causes, medical reasons of the patient, staff-related causes, patient-related reasons, other causes that led to case cancellation, and whether a preoperative visit by anaesthetists had been done. A Pareto chart has been used to identify the main reasons that accounted for 80% of avoidable surgical cancellations, thereby guiding future improvement strategies. A total of 181 of the scheduled operations were cancelled. Many patients were female, and 7.2% were paediatric surgery patients. (82.3 %) did not suffer from chronic illness, and notably, a greater proportion (98.3%) of the patients had no preoperative anaesthetic assessment. Many patients were scheduled under general anaesthesia, and 24.3% were scheduled for general surgery. Cancellations were mainly due to administrative reasons (64.1%), followed by patient-related causes (24.3%), and were less likely due to other reasons (9.9%). Among patient-related cancellations, the most frequent issue was patients not showing up. The foremost administrative cause was a hospital staff strike. Among other causes, the unavailability of ICU beds was the most mentioned reason. This study highlights the key factors contributing to surgical cancellations at TUH. Addressing these reasons mainly through improved preoperative preparation, better resource allocation, and targeted interventions can improve the efficiency of surgical services, minimise delays, and improve overall patient care. Further research and focused strategies are recommended to optimise hospital surgical services.